Brucella terminal ileitis: a rare cause of intestinal obstruction about a case - Ayala Correa, Alejandro Antonio; Grande Zamora, Irving Yair; Platas Galván, Santos Enrique; González Rivera, Oswaldo Natanael (International Journal of Research in Medical Sciences, 2021)
Brucellosis is a bacterial zoonosis transmitted by contact with fluids from infected domestic animals, by consumption of unpasteurized milk products, or by inhalation of infected aerosols. Systemic infection has clinical manifestations from asymptomatic cases to those that are fatal. Focal infections occur in 30% of cases and affect any organ. Gastrointestinal manifestations are rare and unspecific. We reported the case of a patient with antithrombin III deficiency who presented with a clinical picture of abdominal pain at the emergency department, with failure of conservative treatment and with progression to acute abdomen, for which surgical treatment was offered, resolving the condition of intestinal obstruction and taking a biopsy that confirmed terminal brucella ileitis, antibiotic treatment and intestinal rest were indicated with successful results. Brucella terminal ileitis is an unusual manifestation of brucellosis. History of consumption of unpasteurized milk and derivatives and contact with livestock should be carefully examined in patients with acute abdomen in Brucella endemic countries. This will lead to a full and uncomplicated recovery from this disease.